Smartphone Based Testing in Qur'an Hadith Education - Cholis, Nur; Fahyuni, Eni Fariyatul (Indonesian Journal of Islamic Studies, 2024)
General Background: The use of technology in educational assessments has become increasingly important for evaluating student competencies. Specific Background: In Tsanawiyah madrasas, the implementation of smartphone-based assessments (SBT) in Qur'an-Hadith subjects presents unique challenges and opportunities, yet empirical analysis of its application remains limited. Knowledge Gap: Previous studies have not comprehensively addressed the operational aspects and the context of SBT implementation in this specific educational setting. Aims: This research aims to analyze the application of SBT as an assessment medium in Tsanawiyah madrasas, focusing on its implementation, infrastructure, advantages, and challenges. Results: The findings indicate that the SBT is aligned with the standards set by the Educational Standards, Curriculum, and Assessment Agency (BSKAP) and is generally well-received, supported by adequate infrastructure and enthusiasm from educators and students. However, challenges such as network instability, power outages, and proctoring issues impede its effectiveness. Novelty: This study provides a qualitative insight into the practical dynamics of SBT in an Islamic educational context, emphasizing both supportive and obstructive factors. Implications: The results highlight the need for improved technological support and training to mitigate challenges, suggesting that enhanced collaboration between educators and technical teams could foster more effective assessment practices in madrasas. Highlights: Alignment with Standards: SBT implementation adheres to guidelines set by educational authorities, ensuring compliance. Infrastructure and Support: Adequate facilities and collaboration among educators and technicians contribute to successful assessment. Challenges Faced: Issues like network instability and power outages hinder effective smartphone-based testing. Keywords: Smartphone-based assessment, Qur'an-Hadith, Tsanawiyah madrasas, educational technology, challenges.